Combined [18F]-Fluoroethylcholine PET/CT and 99mTc–Macroaggregated Albumin SPECT/CT Predict Survival in Patients With Intermediate-Stage Hepatocellular Carcinoma. (July 2018) - Hartenbach, Markus; Weber, Stefan; Pilz, Magdalena; Hartenbach, Sabrina; Zacherl, Mathias J.; Paprottka, Philipp M.; Tiling, Reinhold; Bartenstein, Peter; Hacker, Marcus; Haug, Alexander R.; Albert, Nathalie L.
Abstract : Aim: The aim of this study was to retrospectively analyze the prognostic value of combined 99m Tc–macroaggregated albumin (MAA) SPECT/CT and [ 18 F]-fluoroethylcholine (FEC) PET/CT before radioembolization for survival of patients with intermediate-stage hepatocellular carcinoma. Methods: Twenty-four patients with known hepatocellular carcinoma Barcelona Clinic Liver Cancer stage B were eligible for this analysis. All patients were scheduled for radioembolization and received a pretherapeutic [ 18 F]FEC PET/CT scan as well as 99m Tc-MAA SPECT/CT for hepatopulmonary shunting. Laboratory and semiquantitative PET parameters and morphologic and metabolic (intersection) volumes of MAA and FEC were evaluated. Spearman correlation with overall survival, receiver operating curve analyses, univariate and multivariate Cox regression, and Kaplan-Meier-analysis was applied. Results: All patients (5 female/19 male) are deceased within the observational period. Median survival was 395 days (±51 days; range, 23–1122 days). The percentage of hypervascularized metabolically active tumor volume (vascularized tumor ratio; defined as high MAA and FEC uptake) correlated significantly with survival. Vascularized tumor ratio was a significant predictor in univariate and multivariate analyses ( P = 0.026; hazard ratio, 11.65; 95% confidence interval, 1.62–83.73; P = 0.015). Statistical significance was not reached by all other variables in multivariate analysis. Receiver operating curve analysis for 1-year survival revealed an area under the curve of 0.77 ( P = 0.024) for vascularized tumor ratio. At a cutoff value of 9%, sensitivity, specificity, and positive and negative prediction were 83%, 67%, and 71% and 80% ( P = 0.036). Patients with a higher tumor vascularization had a median survival of 274 ± 80 versus 585 ± 284 days ( P = 0.015). Conclusions: Hepatocellular carcinoma with high vascularization in metabolic active areas as assessed by combined FEC PET/CT and Tc-MAA SPECT/CT represents an unfavorable subgroup with reduced overall survival after radioembolization.